An investigation of the Inclusion of Critical Reading Strategies in Jordanian EFL Textbooks: A Content Analysis - husban, naima (DIRASAT: EDUCATIONAL SCIENCES, 2016)
This study aimed to examine the inclusion of critical reading strategies in the Action Pack 9 textbook by using content analysis. The findings of the study reveal that some critical reading strategies were moderately included in the textbook, like annotating, previewing, scanning and skimming, and facts versus conclusion, whereas some other strategies were limitedly included, such as classifying or categorizing, and comparing and contrasting, Meanwhile, generating questions was not included at all. These findings revealed that the inclusion of critical reading skills was somewhat imbalanced in the Action Pack9 textbook. Based on these results, it is recommended that the results of this study be taken into consideration when reforming EFL textbooks and that the content of other textbooks be analyzed.